Effects of the self-management training program on self-management behavior and blood pressure levels among elderly people with hypertension - Bumrungsuk Swanee (Sciendo, 2022)
To determine the effects of the Self-Management Training Program on self-management behavior and blood pressure (BP) levels among elderly people with hypertension (HT).